Strategic Integration of Client Servicing and Digital Marketing for Competitive Advantage - Joshi, Sakshi (ATLAS SkillTech University, 2025)
During my internship journey, I had the privilege of working in two distinct yet complementary roles, each offering unique insights and learning experiences that have greatly contributed to my professional development. At Scarecrow M&C Saatchi, I served as a Client Servicing Intern, where I was deeply involved in understanding the intricacies of brand management and advertising. My role encompassed studying client brands, conducting competitor analyses, and observing market strategies to inform campaign planning and execution. I worked closely with senior brand managers, including my mentor Monil Shah, who guided me in developing strategic advertising solutions tailored to specific target audiences. My responsibilities also included brainstorming creative ideas, visualizing campaigns, and rebranding efforts, which sharpened my skills in client servicing and strategic planning. The experience provided a comprehensive understanding of how to translate client needs into effective marketing strategies, offering a strong foundation in the advertising industry. At Digital Dojo, I held the position of Digital Marketing Executive Intern, where I focused on the dynamic and fast-paced world of digital marketing. My work involved Content Creation & Marketing, Performance Marketing, and Media Planning, with a particular emphasis on LinkedIn marketing, content development, and business development strategies. Under the mentorship of Sachin Sadare, I gained hands-on experience in creating and executing digital marketing campaigns, developing content that drove brand awareness, and generating leads for the company. I was also responsible for managing Digital Dojo’s online presence, bidding for projects on Upwork, and engaging with industry professionals to foster B2B connections. Additionally, I had the opportunity to assist in creating web stories and optimizing SEO strategies for the company’s website. These experiences have significantly enriched my understanding of the digital marketing landscape, equipping me with practical skills that are crucial for a career in this field. Both roles have been instrumental in shaping my professional journey, providing me with a well-rounded perspective on the intersection of traditional advertising and digital marketing. The knowledge and skills acquired through these internships have prepared me to navigate the complexities of the marketing and advertising industry with confidence and creativity.
Project Report on Strategic Integration of Client Servicing and Digital Marketing for Competitive Advantage (2023-2025) Under the Guidance of Prof. Mukul Bhatt
Keywords: Digital Marketing; Marketing; SEO; Content Creation; professional development